(3x+y-z)p + (x+y-z)q = 2(z-y)
We have a quasilinear first-order PDE.
"p=\\frac{\\partial z}{\\partial x},\\ q=\\frac{\\partial z}{\\partial y}."
Characteristic system of the equation:
"\\frac{dx}{3x+y-z}=\\frac{dy}{x+y-z}=\\frac{dz}{2(z-y)}"
We will find two independent particular solutions of this system.
Each ratio is equal to "\\frac{-dx+3dy+dz}{0}." So "-dx+3dy+dz=0." Then "x-3y-z=C_1\\text{ is the first solution of the system}."
Each ratio is equal to "\\frac{dx-dy+dz}{2x-2y+2z}=\\frac{dx+dy-dz}{4x+4y-4z}."
"\\frac{d(x-y+z)}{x-y+z}=\\frac{d(x+y-z)}{2(x+y-z)}."
On integrating both sides we get:
"\\ln (x-y+z)=\\frac{1}{2}\\ln (x+y-z)+\\ln C_2.\\\\\n\\frac{x-y+z}{\\sqrt{x+y-z}}=C_2\\text{ is the second solution of the system}."
Then the general solution of our equation can be written as
"\\Phi(x-3y-z; \\frac{x-y+z}{\\sqrt{x+y-z}})=0"
where "\\Phi" is an arbitrary function of two variables.
Comments
Leave a comment